Employee Ownership and Work Motivation: How Much Does Remuneration Matter? - Amadi, Nduka (2013)
This research is concerned with investigating the relationship between profit sharing arrangements and work motivation in an employee-owned business. The specific aims of the research are to examine the relationship between profit sharing and motivation, examine the effect of the mechanism of profit sharing on motivation and to highlight the differences that monetary motivation incentives have on early career and senior employees. For the purpose of this research data was gathered through the use of qualitative research interviews and in particular semi-structured interviews with employees of an employee-owned firm. This research provides a qualitative examination of the relationship between remuneration and motivation in order to add to the body of knowledge on the subject, which is largely quantitative. The findings of this research are that profit sharing can be an effective motivational tool provided that other aspects of the work environment are appropriate and a market rate salary is paid. Furthermore the research found that the mechanism of profit share distribution has an effect on motivation and that career stage has a bearing on whether monetary incentives can effectively motivate employees.